Transcriptional organization of the Salmonella Typhimurium phage P22 pid ORFan locus - Wolput, S.; Makumi, Angela; Wicke, L.; Bäcker, L.E.; Cenens, W.; Briers, Y.; Wenner, N.A.; Owen, S.V.; Hinton, J.C.D.; Lavigne, R.; Aertsen, A. (MDPI, 2022)
Many phage genes lack sequence similarity to any other open reading frame (ORF) in current databases. These enigmatic ORFan genes can have a tremendous impact on phage propagation and host interactions but often remain experimentally unexplored. We previously revealed a novel interaction between phage P22 and its Salmonella Typhimurium host, instigated by the ORFan gene pid (for phage P22 encoded instigator of dgo expression) and resulting in derepression of the host dgoRKAT operon. The pid gene is highly expressed in phage carrier cells that harbor a polarly located P22 episome that segregates asymmetrically among daughter cells. Here, we discovered that the pid locus is fitted with a weak promoter, has an exceptionally long 5′ untranslated region that is instructive for a secondary pid mRNA species, and has a 3′ Rho-independent termination loop that is responsible for stability of the pid transcript.